Cost-effective modeling for natural resource distribution systems - Al-Ayyoub, Abdel-Elah (Parallel algorithms and applications, 2004)
Pipe systems are in the cores of many real life applications including water, oil and gas distribution as well as air-conditioning and compressed air management. Modeling and analysis of flow in pipe networks is of great practical significance in all these areas. Pipe networks are usually made up of thousands of components such as pipes, pumps, valves, tanks and reservoirs. One common way to model these networks is by using systems of linear equations. Practical sizes for these systems usually involve exhaustive calculations that require high computational power. This work emphasizes the design and evaluation of a concurrent system for modeling pipe networks using linear algebraic methods. The proposed approach offers low-cost and high-speed alternative to traditional solutions. It uses a unified row mapping method that exploits the properties of the pipe network matrix in order to achieve a balanced load distribution. This approach is based on cluster computing as a viable alternative to the expensive massively parallel processing systems. The performance of the proposed approach is investigated on a cluster of workstations connected by general-purpose networks.